Impacts of temperature and coating pigment ratios on the corrosion rate of ss400 steel - Budiarto, Untung; Firdhaus, Ahmad; Hakim, Muhammad Luqman; Tuswan, Tuswan; Yusuf, Fauzan Ammar Fata (Universitas Gadjah Mada, 2024)
Steel is the primary shipbuilding material; however, it erodes quickly. Adequate protection requires hard, durable, and adhesive coatings. This study examines how aluminium-graphite pigment and heat treatment affect epoxy-coated SS400 steel plate corrosion, adhesion, and coating resilience. This study used a 1:1 and 3:1 pigment ratio with 100°C and 150°C heat treatment. The coating layer was 250 μm thick and comprised 80% epoxy and 20% aluminum-graphite. The maximum adhesion strength, 19.62 MPa, was achieved with an aluminium-graphite pigment ratio of 1:1 and 100°C heat treatment. The top coating resistance was 6.86 Joules under identical conditions. The lowest corrosion rate, 0.047 mmpy, was at a 3:1 aluminum-graphite ratio and 150°C heat treatment. This discovery has significant consequences for shipbuilding steel corrosion resistance.